A rare case of unruptured ectopic pregnancy in a rudimentary horn with a dead foetus of sixteen weeks - Saraladevi, Rama; Laxmi, B. Vijaya; Madhavi, J.; Radha, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Ectopic pregnancy in a rudimentary horn of bicornuate uterus is a rare type of ectopic pregnancy. It also called as cornual pregnancy. It is difficult to differentiate from tubal pregnancy. The clinical features are similar to that of tubal ectopic pregnancy. The diagnosis is made by operative finding, that is, position of the attachment of the round ligament to the gestational sac, which is always lateral to the cornual pregnancy, whereas in tubal pregnancy the round ligament lies medial to the gestational sac.